2000
DOI: 10.1046/j.1365-2672.2000.01209.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of quercetin-3-glucoside in gnotobiotic rats associated with human intestinal bacteria

Abstract: Aim: The two bacterial species, Eubacterium ramulus and Enterococcus casseli¯avus, which had previously been isolated from human faeces using the¯avonoid quercetin-3-glucoside as the growth substrate, were tested for their ability to utilize this compound in vivo. Methods and Results: Germ-free rats were associated with Eu. ramulus and subsequently with Ent. casseli¯avus and vice versa. Identi®cation and enumeration of the bacterial cell counts in faeces and intestinal contents were performed by whole cell¯uor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 51 publications
1
42
0
Order By: Relevance
“…Which one of these two recycling processes is more important in the disposition of flavonoids has not been determined. However, the important role played by the intestinal microflora in these recycling processes has been confirmed by Schneider et al (2000) who showed significant differences in the pattern of flavonoid metabolites recovered in urine, depending on whether or not bacteria are present in the gut. It is generally believed that these recycling processes may provide a prolonged exposure period for dietary flavonoids.…”
Section: Discussionmentioning
confidence: 93%
“…Which one of these two recycling processes is more important in the disposition of flavonoids has not been determined. However, the important role played by the intestinal microflora in these recycling processes has been confirmed by Schneider et al (2000) who showed significant differences in the pattern of flavonoid metabolites recovered in urine, depending on whether or not bacteria are present in the gut. It is generally believed that these recycling processes may provide a prolonged exposure period for dietary flavonoids.…”
Section: Discussionmentioning
confidence: 93%
“…Cycasin is hydrolytically activated by bacterial enzymes in conventional rats but is excreted unchanged in germ-free animals. Differences in biotransformation between germ-free and conventional animals or animals associated with specific microbial species have also been reported for many other xenobiotics, including propachlor (Bakke et al, 1980), 1-nitropyrene (El-Bayoumy et al, 1983), and quercetin (Schneider et al, 2000). A direct involvement of bacterial enzymes in the biotransformation has been demonstrated for some of these compounds.…”
mentioning
confidence: 87%
“…It is found in fruits, vegetables and plant-derived beverages such as tea and wine [122]. Gut microflora in the large intestine metabolize rutin to a variety of compounds that include quercetin and phenol derivatives such as 3,4-dihydroxyphenylacetic acid (DHPAA), 3,4-dihydroxytoluene (DHT), 3-hydroxyphenylacetic acid (HPAA), and 4-hydroxy-3-methoxyphenylacetic acid (homovanillic acid, HVA) [122][123][124]. Rutin metabolites, particularly those that include vicinal hydroxyl groups in their structure such as 3,4-dihydroxyphenylacetic acid (DHPAA) and 3,4-dihydroxytoluene (DHT), are powerful inhibitors of the formation of CML and fluorescent derivatives (370-440 nm and 335-385 nm) in histone H1 caused by ADP-ribose.…”
Section: Flavones Flavonols Flavanones and Flavanonolesmentioning
confidence: 99%